STUDY ON THE EFFECT OF MULBERRY LEAF PRESERVATION AND ITS IMPACT ON COCOON CROP AND COCOON QUALITY IN SILKWORM BOMBYX MORI LINN. - KUMAR, VINEET; HIMANTHARAJ, M.T.; RAJAN, R.K.; SINGH, G.P.; MATHUR, V.B.; KAMBLE, C.K.; DATTA, R.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
Different types of mulberry leaf preservation bags for young age silkworm rearing has been designed, fabricated and evaluated. Based on the maximum leaf moisture percentage (77.06%) and minimum leaf driage percentage (2.38%) among different types of leaf preservation bags, the PGP bag was selected and rearing was conducted. The rearing and reeling parameters showed that the PGP bag is better over others and suitable for leaf preservation for chawki age. Further, the table of analysis of varience showed the significant difference in all the rearing parameters except ERR by weight, whereas, the reeling parameter viz, reelability was observed highly significant among the different types of leaf preservation bags.